Direct measurement of the critical cooling rate for the vitrification of water - Nathan J. Mowry; Constantin R. Krüger; Marcel Drabbels; Ulrich J. Lorenz (Physical Review Research)
The vitrification of aqueous solutions through rapid cooling is a remarkable achievement that launched the field of cryo-electron microscopy (cryo-EM) and has enabled the cryopreservation of biological specimens. For judging the feasibility of a vitrification experiment, the critical cooling rate of pure water is a frequently cited reference quantity. However, an accurate determination has remained elusive, with estimates varying by several orders of magnitude. Here, we employ time-resolved electron microscopy to obtain a precise measurement of this quantity. We use shaped microsecond laser pulses to briefly melt an amorphous ice sample before flash freezing it with a variable, well-defined cooling rate. This allows us to directly measure the critical cooling rate of water, which we determine to be 6.4×10^{6}K/s. This result provides important insights into the question of how closely the conformational ensembles in plunge-frozen cryo samples reflect the structure of a protein at room temperature. Moreover, our experimental approach expands the toolkit of microsecond time-resolved cryo-EM, an emerging technique, in which a cryo sample is flash melted and revitrified with a laser pulse in order to enable time-resolved observations of protein dynamics.